A 20-year journey on the invention of vibrational photothermal microscopy - Cheng, Ji-Xin (Nature methods, 2025)
Vibrational microscopy opens a new window onto understanding life at the molecular level. Yet the vibrational signals from chemical bonds are weaker than the fluorescence signal from a dye by many orders of magnitude. Detecting such weak signal from a tight focus under a microscope is extremely challenging. I have devoted my career to overcoming such a daunting barrier through the development of advanced chemical microscopes over the past 25 years. In this historical Comment, I am honored to share my journey of serendipity-driven innovation and entrepreneurship in the growing field of chemical imaging, with a focus on the invention of vibrational photothermal microscopy.